Profile of risk factors for acoustic trauma in 105 Howitzer Cannon shooter students - Kristianti, Asti; Ramdhani, Sony; Amanda Pramesti, Dea (ACTA Medical Health Sciences, 2024)
Acoustic trauma is hearing loss caused by short periods of high-frequency noise. Hearing loss can occur in the military because it uses the main tools of the weaponry system, such as guns, military vehicles, and explosions. This research aims to determine the description of risk factors for acoustic trauma, patterns of hearing protector use, and ear complaints among students of Pusat Pendidikan Artileri Medan (Pusdik Armed) who performed 105 Howitzer Cannon shooting practice. This study used a descriptive method with a cross-sectional design on the students of the Pusdik Armed who practised shooting with 105 Howitzer Cannons. The sampling technique used was total sampling with 103 students. The research instrument is data from questions and blood pressure checks. The results showed a description of the risk factors for acoustic trauma in Pusdik Armed Students who performed Howitzer 105 Cannon shooting practice, which were primarily due to high noise exposure, smoking history, use of PLDs, failure to wear protectors (a small percentage), and use of ototoxic drugs; no one had hypertension and a family history of hearing loss. The patterns of wearing hearing protection during the 105 howitzer cannon firing exercises were gathered from the students who carried out the practice. Additionally, some wore them throughout practice. When it came to ear complaints prior to practice, the majority of students had none before or after cannon shooting practice. Therefore, using ear protective equipment for cannon shooters is necessary. DOI : 10.35990/amhs.v2n3.p130-137 REFERENCES Chadha, S., Kamenov, K., & Cieza, A. (2021). The world report on hearing, 2021. Bulletin of the World Health Organization, 99(4), 242–242A. Orru, H., Luha, A., Pindus, M., Jõgeva, R., Vahisalu, M., Lekk, U., et al. (2020). Hearing loss among military personnel in relation to occupational and leisure noise exposure and usage of personal protective equipment. Noise & Health, 22(107), 90. Retrieved from /pmc/articles/PMC8000139/ Mayasari, D., & Khairunnisa, R. (2017). Pencegahan noise induced hearing loss pada pekerja akibat kebisingan. Jurnal Argomed Unila, 4(2), 354–360. Eryani, Y. M., Wibowo, C. A., & Saftarina, F. (2017). Faktor risiko terjadinya gangguan pendengaran akibat bising. Medula, 7(4), 112–117. Nieman, C. L., & Oh, E. S. (2020). Hearing loss. Annals of Internal Medicine, 173, ITC81–96. Yehudai, N., Fink, N., Shpriz, M., & Marom, T. (2017). Acute acoustic trauma among soldiers during an intense combat. Journal of the American Academy of Audiology, 28(5), 436–443. Chan, Y., & Goddard, J. (2019). J. Lee’s Essential Otolaryngology: Head and Neck Surgery (12th ed., pp. 394–396). McGraw-Hill. Esquivel, C. R., Parker, M., Curtis, K., Merkley, A., Littlefield, P., Conley, G., et al. (2018). Aural blast injury/acoustic trauma and hearing loss. Military Medicine, 183(1), 78–82. (Duplikat referensi no. 2, bisa dihapus jika memang sama) Sasongko, S., & Suteja. (2015). Trauma akustik yang berkaitan dengan prajurit penembak meriam Howitzer 105. In Cimahi: LPPM Unjani (pp. 130–133). Occupational Safety and Health Administration. (n.d.). Occupational noise exposure. Retrieved from https://www.osha.gov/laws-regs/regulations/standardnumber/1910/1910.95 Peraturan Menteri Ketenagakerjaan Republik Indonesia. (2018). Keselamatan dan Kesejahteraan Kerja Lingkungan Kerja. (Duplikat referensi no. 8, bisa dihapus jika memang sama) Toivonen, M., Pääkkönen, R., Niemensivu, R., Aarnisalo, A., & Mäkitie, A. A. (2023). Acute acoustic trauma after exposure to assault rifle noise among conscripts in the Finnish Defence Forces: A population-based survey. International Journal of Environmental Research and Public Health, 20(4). Medina-Garin, D. R., Dia, A., Bedubourg, G., Deparis, X., Berger, F., & Michel, R. (2016). Acute acoustic trauma in the French armed forces during 2007–2014. Noise & Health, 18(85), 297–302. World Health Organization. (2015). Hearing loss due to recreational exposure to loud sounds. Switzerland: WHO. Kristianti, A., & Nurrokhmawati, Y. (2020). Gambaran pola penggunaan personal listening devices (PLDs), dan hasil audiogram pelajar SMPN 3 Cimahi. Medika Kartika: Jurnal Kedokteran dan Kesehatan, 3(2), 103–112. Ningsih, D. L., Marliyawati, D., & Yunika, K. (2018). Pengaruh merokok terhadap gangguan pendengaran pada usia dewasa muda. Jurnal Kedokteran Diponegoro, 7(2), 1380–1390. Li, X., Rong, X., Wang, Z., & Lin, A. (2020). Association between smoking and noise-induced hearing loss: A meta-analysis of observational studies. International Journal of Environmental Research and Public Health, 17(4), 1201. Nasution, D. S., & Nasution, M. E. S. (2020). Hubungan hipertensi dengan gangguan pendengaran di Rumah Sakit Bhayangkara TK II Medan. Jurnal Pandu Husada, 1(4), 221–225. Wang, B., Han, L., Dai, S., Li, X., Cai, W., Yang, D., et al. (2018). Hearing loss characteristics of workers with hypertension exposed to occupational noise: A cross-sectional study of 270,033 participants. BioMed Research International, 2018, 4–5. (Duplikat referensi no. 12, bisa dihapus jika memang sama) (Duplikat referensi no. 4, bisa dihapus jika memang sama) Nurul, S., Meutia, R., Adawiyah, R., Tette, D., & Sofyan, A. (2022). Obat ototoksik (Ototoxic medications). Jurnal Medical Profession (MedPro), 4(1), 49–57. Yulianti, Y., & Mahdiani, S. (2015). Gangguan pendengaran penderita tuberkulosis multidrug resistant. Oto Rhino Laryngologica Indonesiana, 45(2), 83. Benokri, H., Rianto, B., & Sastrowijoto, S. (2020). Gangguan pendengaran sensori pada pasien pasca pengobatan tuberkulosis multidrug resistant selama 6 bulan. Yogyakarta: Universitas Gadjah Mada. Fitriyani, B. B., & Wahyuningsih, S. A. (2016). Hubungan pengetahuan tentang alat pelindung telinga (ear plug) dengan kepatuhan penggunaannya pada pekerja bagian tenun departemen weaving SL PT. Daya Manunggal. Unnes Journal of Public Health, 5(1), 102. Kwak, C., & Han, W. (2021). The effectiveness of hearing protection devices: A systematic review and meta-analysis. International Journal of Environmental Research and Public Health, 18(21), 11693.